Role of Chaperone-Mediated Autophagy Dysfunctions in the Pathogenesis of Parkinson’s Disease - Sala, Gessica; Marinig, Daniele; Arosio, Alessandro; Ferrarese, Carlo (Frontiers in Molecular Neuroscience, 2016)
Chaperone-mediated autophagy (CMA) represents a selective form of autophagy involved in the degradation of specific soluble proteins containing a pentapeptide motif that is recognized by a cytosolic chaperone able to deliver proteins to the lysosomes for degradation. Physiologically, CMA contributes to maintain crucial cellular functions including energetic balance and protein quality control. Dysfunctions in CMA have been associated to the pathogenesis of several neurodegenerative diseases characterized by accumulation and aggregation of proteins identified as CMA substrates. In particular, increasing evidence highlights the existence of a strong relationship between CMA defects and Parkinson’s disease (PD). Several mutations associated with familial forms of PD (SNCA, LRRK2, UCHL1 and DJ-1) have been demonstrated to block or reduce the activity of CMA, the main catabolic pathway for alpha-synuclein. CMA dysfunctions also lead to a mislocalization and inactivation of the transcription factor MEF2D that plays a key-role in the survival of dopaminergic neurons. Furthermore, reduced levels of CMA markers have been observed in post-mortem brain samples from PD patients. Aim of this review is to provide an organic revision of evidence for the involvement of CMA dysfunctions in the pathogenesis of PD. Updated findings obtained in patient’s specimens will be resumed, and results deriving from in vivo and in vitro studies will be discussed to evidence the current knowledge on the molecular mechanisms underlying CMA alterations in PD. Finally, the opportunity of up-regulating CMA pathway as promising neuroprotective strategy will be considered.